2017
DOI: 10.1093/annonc/mdw547
|View full text |Cite
|
Sign up to set email alerts
|

Management of chronic lymphocytic leukemia (CLL) in the elderly: a position paper from an international Society of Geriatric Oncology (SIOG) Task Force

Abstract: Chronic lymphocytic leukemia (CLL) mainly affects older people: the median age at diagnosis is > 70 years. Elderly patients with CLL are heterogeneous with regard both to the biology of their disease and aging. Following the diagnosis of CLL in an elderly individual, careful risk assessment is essential when treatment options are evaluated. This includes not only clinical staging and evaluation of disease-specific prognostic biomarkers such as 17p deletion and TP53 mutation, but also of comorbidities, physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 94 publications
1
51
0
Order By: Relevance
“…This older population is prone to a greater incidence and severity of comorbidities, as well as disease-and infection-related death, all of which may lead to delays in therapy initiation and poorer outcomes. [15][16][17][18] OS rates among all treated patients were modest (median 52.4 months for first-line therapy and 33.7 months for second-line therapy). Although our study does not permit causal inferences, we observed that rituximab monotherapy and rituximab-containing chemoimmunotherapy combinations were associated with favorable survival outcomes when compared to chlorambucil monotherapy in the front-line setting.…”
Section: Letters To the Editormentioning
confidence: 91%
“…This older population is prone to a greater incidence and severity of comorbidities, as well as disease-and infection-related death, all of which may lead to delays in therapy initiation and poorer outcomes. [15][16][17][18] OS rates among all treated patients were modest (median 52.4 months for first-line therapy and 33.7 months for second-line therapy). Although our study does not permit causal inferences, we observed that rituximab monotherapy and rituximab-containing chemoimmunotherapy combinations were associated with favorable survival outcomes when compared to chlorambucil monotherapy in the front-line setting.…”
Section: Letters To the Editormentioning
confidence: 91%
“…5,[10][11][12] Although eligibility criteria for studies of anti-cancer/-MM agents have traditionally relied on age cut-offs and performance status, geriatric and MM-specific frailty assessments are just beginning to be incorporated into more accurate stratification plans of treatment algorithms. 6,7,11,12 Similarly to MM patients, geriatric assessments (GA) have been defined for patients with chronic lymphocytic leukemia (CLL) 8,13,14 and myelodysplastic syndrome (MDS), 15,16 where determination of frailty versus fitness has moved into clinical practice. However, solutions as to how they might be more uniformly used and valued in their daily pratice have not been fully determined.…”
Section: Introductionmentioning
confidence: 99%
“…2 However, CLL is mainly a disease of the elderly with many patients presenting at diagnosis with significant comorbidities that may affect treatment decisions and outcome. 3 Moreover, in recent years, the complex karyotype (CK) emerged as a prognostic biomarker associated with an inferior outcome 4,5 and worse response to treatments including novel drugs. 6,7 We therefore set out to analyze the prognostic relevance of comorbidities and of CK in relation to the CLL-IPI.…”
mentioning
confidence: 99%
“…Indeed, relevant comorbidities may shorten life expectancy and may reduce treatment tolerance, 3,17 and modern treatment algorithms recommended evaluating not only age, clinical staging, and disease-specific prognostic biomarkers, but also comorbidities to guide clinical decisions, 13,18 particularly in the era of novel drugs. 19 However, the prognostic impact of comorbidities and of the CK in the era of mechanism-based treatment needs to be specifically addressed in larger series of patients treated for longer periods of time because in our cohort of CLL, these agents were offered only in more recent years.…”
mentioning
confidence: 99%